Hazard Identification, Risk Assessment and Determining Control Occupational Health and Safety (OHS) In CV C-Maxi Alloycast - Dewi Masri - (ITB Journal Publisher, LPPM ITB, 2022)
CV C-Maxi Alloycast is a company engaged in the casting of household appliances and manufacture of precision products made from aluminum. So it is possible in every activity there is a potential danger. The objectives of this study were to identify potential hazards and assess safety and health risks and to evaluate risk control techniques. This research was conducted on 4 divisions ie warehouse division, casting division, technician division and finishing division. Thus, it can reduce the number of work accident. This research refers to AZ / NZS 4360: 2004 standard using descriptive study method with qualitative analysis based on observation and research form which then analyzed and evaluated for control effort. From the results of the study concluded that the potential danger and risk always exist in every activity, so it is necessary to identify and assess as an effort to create a safe and safe working environment. The results of the identification obtained are 126 risk level, among which 8 low risk level (6%), 57 moderate risk level (45%), and 60 high risk level (48%). Evaluation of risk controls found in the field can be said to have been running quite well just that control should be supported by awareness of workers to OHS in order to create a safe and productive production conditions. Keywords: Hazard Identification, Risk Assessment, Risk Control, Occupational Health and Safety (OHS)